2021
DOI: 10.3390/ijerph18157781
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Patterns of Exclusive and Dual Use of ENDS and Menthol/Non-Menthol Cigarettes among US Youth (Ages 15–17) Using Two Nationally Representative Surveys (2013–2017)

Abstract: The use of electronic nicotine delivery systems (ENDS) among youth in the United States has increased rapidly in the past decade. Simultaneously, while youth cigarette smoking has declined considerably, youth are still more likely to use menthol cigarettes than any other age group. We used nationally representative data on 15–17-year-olds from the Population Assessment of Tobacco and Health (PATH) Study and the National Youth Tobacco Survey (NYTS) (2013–2017) to better understand current cigarette (by menthol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
(87 reference statements)
2
9
0
Order By: Relevance
“…Regarding race/ethnicity, relative to NHW respondents, racial/ethnic minority respondents had lower odds of exclusive e-cigarette and dual use across all grades, which is consistent with previous research [ 2 , 4 , 12 ]. Also, as earlier studies show [ 12 , 13 ], we found that adolescents whose highest parental education was a college degree or more versus less than a high school degree had lower odds of exclusive combustible tobacco product and dual use when compared to no use, but higher odds of exclusive e-cigarette use.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Regarding race/ethnicity, relative to NHW respondents, racial/ethnic minority respondents had lower odds of exclusive e-cigarette and dual use across all grades, which is consistent with previous research [ 2 , 4 , 12 ]. Also, as earlier studies show [ 12 , 13 ], we found that adolescents whose highest parental education was a college degree or more versus less than a high school degree had lower odds of exclusive combustible tobacco product and dual use when compared to no use, but higher odds of exclusive e-cigarette use.…”
Section: Discussionsupporting
confidence: 83%
“…Studies have shown slight sociodemographic differences among adolescents who exclusively use e-cigarettes versus combustible tobacco products. While male adolescents are more likely than females to use e-cigarettes exclusively [ 12 , 13 ], studies have shown comparable rates of exclusive combustible tobacco product use among males and females [ 4 , 12 ]. Unlike exclusive e-cigarette use, which is more common among non-Hispanic White adolescents compared to racial/ethnic minority adolescents, non-Hispanic Black adolescents are more likely to use combustible tobacco [ 2 , 4 ] when compared to non-Hispanic White adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, including PATH in our study ensures comparability with earlier studies. ( Hirschtick et al, 2021 , Patel et al, 2021 , Villanti et al, 2017 ) Second, our current use measure did not distinguish between every day and some day users, even though product use and patterns of use may differ between both groups. However, our estimates are easily compared to other studies using this current use definition[51].…”
Section: Discussionmentioning
confidence: 91%